KONSTRUKSI REALITAS PEMBERITAAN KONFLIK PERBATASAN INDONESIA-MALAYSIA PADA SURAT KABAR KOMPAS DAN MEDIA INDONESIA - Setiadi, Wahyu (Universitas Prof. Dr. Moestopo (Beragama), 2012)
Indonesia DKP Arrest by Malaysian Police into a story framed by Kompas and Media Indonesia?â. The paradigm used in this study is konstruktionis. Constructionist paradigm of looking at the reality of social life is not a natural reality, but the result of the construction. Therefore concentrate on the analysis of a constructionist paradigm is to find how the event or the reality constructed by way of what the construction is formed. In this case, the researchers want to uncover how Kompas and Media Indonesia construct a reality in presenting the news. The method used in this study is a model of framing William A. Gamson. In view Gamson, media discourse is an important element to understand and appreciate the growing public opinion on an issue or event. Framing the useof reason as Gamson Gamson and Modiglani focus point his attention to the study of social movements (social movement). In this case, a lot going on demonstrations and debate within the community in assessing the case.The data collected is of Newspapers News Kompas and Media Indonesia on the issue of August 16 to 23 2010. I researched the whole news story amounted to 16 consisting of 9 comes from Compass, and 7 are from Media Indonesia. In addition, there are additional data in the form of interviews with the author Kompas and Media Indonesia. Based on the results of the study, no significant difference of the newspapers in presenting the news. This is mostly caused by the newspaper ideology. Both media also have a framing strategies are different from each other. News framing strategy can be seen from the angel news writing, by the respondents, the choice of words, use of metaphor and so on. So the news can be packaged in such a way and constructed in accordance with the mediaâs desire. Compass has an ideology that is based on a sense of humanity, always presenting news calm and avoid the use of words and the negative connotations that enhance the readerâs emotions. Meanwhile, Indonesiaâs national media gave rise to high subjectivity in reporting on this case. Media Indonesia is quite sharp in criticizing the governmentâs performance.